A GEOLOGIC INTERPRETATION OF SEISMIC PROFILES IN PRINCE WILLIAM SOUND, ALASKA - VON Huene,Roland; Shor,George G.; Reimintz,Erk (1965)
A series of seismic reflection profiles were made during the summer of 1964 in the northeastern part of Prince William Sound, Alaska. Three rock units recognized in the profiles are (1) the ice-sculptured metamorphic basement overlain by (2) probable glacial drift, and (3) Holocene marine sediments. Channels in the basement may have been formed in part by faulting as well as glacial scour, and have been extensively modified by fill of units (2) and (3), so that the present seafloor does not closely represent the effects of glaciation. The Holocene strata have been faulted but the vertical separation is small, suggesting that the sound reacts as a unit to regional tectonism.